Parantipathes pluma Opresko & Molodtsova 2021, n. sp. - Opresko, Dennis M.; Molodtsova, Tina N. (Zenodo, 2021)
Parantipathes pluma n. sp. (Figs 6–8) urn:lsid:zoobank.org:act: 7E0195DB-65A4-4DD9-9320-C013B125012A Parantipathes sp. Brugler et al . 2013: fig. 7A, 7D. Material examined. Holotype: USNM 1093058 (SEM stub 503), N. Pacific, central Aleutian Islands, S. of Amlia Island, ROV Jason II, Dive 95 (Field Identification Number: J 2095-2-7-4), 51.8116°N, 173.8328°W, 843 m, coll. R. Stone, 25 July 2004 (specimen dry). Paratype : USNM 1498742 (SEM stub 510), N. Pacific, Bering Sea, Zhemchug Canyon, F / V Cape Flattery , 58.5395°N, 175.0640°W, 977 m, coll. J. Hoff, 10 Jul 2016. Other Material : USNM 1093061, N. Pacific, central Aleutian Islands, Bobrof Island Pass, ROV Jason II, Dive 106 (Field Identification Number: J 2106-7-1), 51.8924°N, 177.2863°W, 936 m, coll. R. Stone, 7 Aug 2004; USNM 1482130, N. Pacific, central Aleutian Islands, SW of Adak Island, F/ V Ocean Olympic , 51.5270°N, 177.0170°W, 329 m, coll. G. Nightengale, Oct 2004. Diagnosis . Tall colonies, monopodial, unbranched or sparsely branched to the second order. Stem and branches pinnulate. Pinnules mostly simple, up to 13 cm long, arranged bilaterally along the stem, and, in varying degrees of regularity within and between colonies, with two to three rows on each side of axis, and in alternating semispiral groups typically consisting of two or three, and very rarely four pinnules. Pinnular density very variable depending on specimen, location on corallum, number of pinnules per group, and spacing of pinnules within and between groups; commonly 13–16 total per cm, but ranging from about 10 to 19 per cm. Pinnular spines usually simple (rarely with apical lobes), smooth, perpendicular to the axis, with 4–5 spines per mm; polypar spines mostly 0.06–0.08 mm tall (maximum about 0.09 mm); abpolypar spines 0.04–0.06 mm. Polyps on pinnules estimated to be 2.8–3.2 mm in transverse diameter with 2.5–3 polyps per cm. Description of holotype. Holotype (USNM 1093058, Fig. 6A) monopodial, without branches, but pinnulate with simple pinnules in multiple rows along the axis. Holdfast and lower unpinnulated section of stem missing; stumps of pinnules present to bottom of remaining part of stem. Apical section of corallum retained. Remaining section of stem 104 cm long (in three broken pieces). Stem diameter 5.7 mm at broken off basal end. Pinnules (Fig 6B) simple, elongate, arranged bilaterally with two or three rows on each side of the axis, and also in groups of two or three pinnules, one from each row. Spacing of pinnules within each group very irregular both along the axis and around it; therefore, the groups of pinnules are often not in clearly defined semispirals. Pinnules within a group mostly 1–2 mm apart, and a clearly defined semispiral group of three pinnules covers an axial distance of about 3.5 mm. Pinnules are 11–13 cm long and 0.4–0.6 mm in diameter near the base, and inclined distally (distal angle 40–60°). Pinnules subequal in length in all rows. Pinnular density very variable, but commonly 11–13 total per cm (range 9–16 per cm). Pinnules in only 4 rows at bottom of stem, with 10 pinnules total per cm. Pinnular spines (Fig. 7) are smooth, triangular in lateral view, mostly standing nearly perpendicular to the axis, but with some inclined distally and a few inclined basally (relative to the direction of the pinnule). The apex can be acute or rounded. On sections of pinnules where the axis is 0.31–0.37 mm in diameter (excluding spines), the polypar spines are typically 0.07–0.08 mm tall (maximum about 0.09 mm), and the abpolypar spines are usually 0.04–0.06 mm tall (maximum about 0.07 mm). On sections of pinnules where the axis is 0.20–0.23 mm in diameter (excluding spines) and the spines are more compressed laterally, the polypar spines are mostly 0.06 mm tall and the abpolypar spines are only slightly smaller. The spines are arranged in axial rows, six or seven of which can be seen in lateral view, and within the rows there are 4–5 spines per mm. On some sections of the pinnules the rows of polypar spines often appear very crowded together when compared to the rows of abpolypar spines. Often the base of the spines extends out along the axis distally and basally forming axial ridges. The polyps are in a very poor state of preservation (colony dry). They are uniserially arranged on the pinnules, often on the upper or lower side such that those on adjacent pinnules on the same side of the corallum tend to face towards each other. The transverse diameter of the polyps is estimated to range from 2.8 to 3.2 mm, but is mostly close to 3 mm, with 2.5 to 3 polyps per centimeter. Description of paratypes and other material . The specimen selected as a paratype of Parantipathes pluma (USNM 1498742) is an almost complete monopodial colony, without branches, but is only half the size of the holotype (Fig. 8A). The stem is 55 cm long (in four broken pieces) and has a basal diameter of 3 by 3.4 mm just above the holdfast. Pinnulation begins about 2.5 cm above the holdfast. As in the holotype, the pinnules are arranged bilaterally, with three rows on each side of the stem, and they are subequal in length in all rows. The longest pinnules are 11 cm long and have a basal diameter of about 0.4 mm. Pinnules (Fig. 8C) are mostly in alternating semispiral groups of three on each side of the axis (very rarely four per group). The pinnular density along most of the stem is about five groups of three pinnules per cm, but because of varying interpinnular distances and the overlap of pinnules on each side of the axis, the total number of pinnules per cm ranges from 14 to 19 per cm, compared to a typical range of 11–13 per cm in the holotype. The semispiral groups of three pinnules cover a distance of 2 to 2.5 mm. The pinnules on lowest part of stem are in groups of two. In places along the stem the pinnular arrangement in rows and semispiral groups becomes very distorted as in the holotype. The pinnules in all rows are inclined distally such that the distal angle they form with the stem is close to 45°, but nearer the top of the stem this increases to about 60°. The interior angle formed between the two posterior rows of pinnules is about 180°; that of lateral and anterior rows is around 120°. The pinnular spines (Fig. 8B) are similar to those in the holotype in being triangular in lateral view, standing nearly perpendicular to the axis. They have an acute to rounded apex. On sections of pinnules 0.2 to 0.32 mm in diameter, the polypar spines are 0.07 to 0.086 mm tall, and slightly larger than the abpolypar spines (0.04 to 0.07 mm). Four or five rows of spines are visible in lateral view, and there are 4–5 spines per mm in each row. On the lower part of some pinnules (5–10 mm above base) the sclerenchyme becomes thickened and the spines on one side of the axis have multiple (usually 2–4) conically-shaped, apical lobes (Fig. 8D). On the lower part of the stem, the spines are up to about 0.09 mm tall and appear to be in clusters, although these spines may have originated as single spines with multiple apical lobes as those on the lower sections of some of the pinnules. Polyps are too poorly preserved to estimate their size or density. The other two specimens assigned to this species (USNM 1093061 and USNM 1482130) are similar to the type in having pinnules up to 13 cm; pinnules in semispiral groups of mainly two or three; and with spines 0.05–0.07 mm tall. In situ photos of USNM 1093061 (Brugler et al . 2013: 7 A) indicate that the colony was very sparsely branched to the second order; however, only a single branch was collected. Genetic data . GenBank Acc. Nos.: USNM 1093058, holotype [KF054491 ( igrW ), KF054637 ( igrN ), and KF054384 ( cox3-cox1) ]; USNM 1093061 [KF054490 ( igrW ), KF054644 ( igrN ), and KF054384 ( cox3-cox1) ]. DNA sequencing studies using the mt gene regions listed above (Brugler et al . 2013), as well as those using nad5-nad1 (Chery et al . 2018), revealed that all haplotypes of the holotype of P . pluma (USNM 1093058) were identical to those of other Pacific Parantipathes specimens, and to Pacific specimens of Lillipathes and Dendrobathypathes Opresko, 2002. Atlantic species of Parantipathes , including P . larix (Esper, 1790), however, fell into a separate subclade. These results suggest either a polyphyletic origin of the Parantipathes morphotype, or a relatively high degree of genetic change and possibly interchange following the isolation of the populations in separate oceanic basins. Comparisons . Parantipathes pluma n. sp. differs from most of the hitherto known species of the genus by its very long pinnules which are typically more than 10 cm long. The new species is superficially similar to the Atlantic species Parantipathes larix in the maximum length of the pinnules (11–13 cm vs. 6–13 cm in P . larix ), number of rows of pinnules (4–6), and in the size of the polypar spines on the pinnules (up to 0.09 mm vs. up to 0.11 mm in P . larix ), but differs in the larger size of the polyps (2.8–3.2 mm vs. 1.6–2.2 mm) and in the lower density of the pinnules (mostly 11–13 per cm vs. 21 per cm). In addition, the distal angle of the pinnules is 80–90° in P. larix and much less in P. pluma , (40–60°), the number of rows of spines seen in lateral view is greater (6–7 vs. 3–4), and the spines can be distinctly curved distally in P. larix but are more at right angles to the axis in P. pluma . As noted above, P. pluma is genetically distinct from P. larix . The one other species of Parantipathes found in the northern Pacific, P . euantha (see Molodtsova & Pasternak 2005 for redescription), which was described from a relatively small colony, differs from Parantipathes pluma in having shorter pinnules (up to 3.8 cm) and smaller polyps (1.9–2.7 mm). The type specimen of P. euantha was preserved in Bouin fixative, so it is not available for genetic studies. Etymology . Species name " pluma " is derived from the Latin " pluma ", meaning "feather", in reference to the general shape of the corallum. Distribution . Known only from the North Pacific at depths ranging from 329 to 977 m. : Published as part of Opresko, Dennis M. & Molodtsova, Tina N., 2021, New species of deep-sea Antipatharians from the North Pacific (Cnidaria: Anthozoa: Antipatharia), Part 2, pp. 401-422 in Zootaxa 4999 (5) on pages 416-420, DOI: 10.11646/zootaxa.4999.5.1, http://zenodo.org/record/5119429 : {"references": ["Brugler, M. R., Opresko, D. M. & France, S. C. (2013) The evolutionary history of the order Antipatharia (Cnidaria: Anthozoa: Hexacorallia) as inferred from mitochondrial and nuclear DNA: implications for black coral taxonomy and systematics. Zoological Journal of the Linnean Society, 169, 312 - 361. https: // doi. org / 10.1111 / zoj. 12060", "Chery, N., Parra, K., Evankow, A., Stein, D., Distel, D., Appiah-Madson, H., Ross, R., Sanon, E., Alomari, N., Johnson, R., Vasovic, A., Horowitz, A., Popa, H., Short, B., Kourehjan, D., Vasquez, D. M., Rodriguez, E., Opresko, D. M. & Brugler, M. R. (2018) Partnering with the Ocean Genome Legacy to advance our understanding of black corals (Order Antipatharia). 15 th Deep-Sea Biology Symposium, Monterey, California, 9 - 14 September 2018. poster presentation. [preprint available from M. Brugler at https: // tidalmarshtaskforce. wixsite. com / uscb / publications]", "Opresko, D. M. (2002) Revision of the Antipatharia (Cnidaria: Anthozoa), Part II, Schizopathidae. Zoologische Mededelingen, Leiden, 76, 411 - 442.", "Esper, E. J. C. (1790) Die Pflanzenthiere in Abbildungen nach der Natur mit Farben erleuchtet nebst Beschreibungen, Pflanzenthiere 1, Lieferung 5, Raspe, Nurnberg, pl. 4. [see also 1792, Pflanzenthiere 2, p. 147] https: // doi. org / 10.5962 / bhl. title. 118730", "Molodtsova, T. N. & Pasternak, F. A. (2005) Redescription of Parantipathes euantha (Pasternak, 1958) (Anthozoa: Antipatharia) from Kurile-Kamchatka Trench. Invertebrate Zoology, 2 (2), 169 - 179."]}